THE STATE OF CHANGES IN THE BIOELECTRICAL ACTIVITY OF THE BRAIN IN PATIENTS UNDERGOING SURGERY USING GENERAL ANESTHESIA WITH STANDART MANAGEMENT OF THE POSTOPERATIVE PERIOD - Tovazhyanskaya, O. L.; Dubivska, S. S.; Grigorov, Yu. B.; Solovyova, E. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The purpose of this work is to determine the functional state of the brain of patients on the basis of the electroencephalogram, which were operated under general anesthesia against the background of the standard management of the postoperative period. The study was conducted in the surgical departments of various profiles on the basis of the Kharkov City Clinical Hospital of Emergency and Emergency Medical Care. prof. A.I. Meshchaninov. The study was conducted with the total number of patients in 86 young, middle-aged and elderly patients with surgical pathology who underwent surgery under general anesthesia. The study of the functional state of the brain by determining the bioelectrical activity of the brain, by conducting an electroencephalogram, was determined in two stages: before surgery and 3-5 days after surgery with general anesthesia. Based on the data obtained, it is possible to recommend an electroencephalogram to assess the functional state of the brain of patients undergoing surgery under general anesthesia. Marked electroencephalographic changes in the period after the operation indicate a deterioration in the functional state of the brain, which are a consequence of the effects of anesthesia, surgical stress, and effects on cognitive function.